Relationships between semen quality and fertility in a population of infertile men in Erbil city: Semen quality and fertility in infertile men - Ameen, Edrees Mohammad; Najim K. Sabir , Fakhir; Mohammed, Sarbaz Ibrahim (Cellular and Molecular Biology, 2022)
The evaluation and the relationships between human semen quality and fertility in infertile males in Erbil city of Iraq is the aim of the present study. Semen quality and fertility were estimated by using semen analysis. The semen analysis parameters were including; the volume of the semen, and sperm (count, motility, morphology, and viability). For this purpose, one hundred fifty infertile and fifty fertile adult males participated. The study was performed from September 2021 to April 2022 in the Infertility care and In vitro fertilization center (IVF). A significant negative correlation was found between infertility% with decreased semen volume (r = - 0.58, p≤0.05), sperm concentration (r = - 0.74, p ≤0.001), total sperm count (r = - 0.68, p≤0.001), sperm morphology (r = - 0.57, p ≤0.01), sperm viability (r = - 0.80, p ≤0.001), total sperm motility (r = -0.80, p ≤0.001), and progressive motility (r = - 0.78, p≤0.001). Regarding fertility. A significant positive correlation was found between fertility% with increased semen volume (r = 0.64, p ≤0.05), sperm concentration (r = 0.76, p ≤0.001), total sperm count (r = 0.78, p ≤0.001), sperm morphology (r = 0.48, p ≤0.01), sperm viability (r = 0.70, p ≤0.001), total sperm motility (r = 0.84, p ≤0.001), and progressive motility (r = 0.75, p ≤0.001. The prevalence of hypospermia, oligozoospermia, teratozoospermia, low sperm viability, and low sperm motility kinetics (asthenozoospermia) in infertile males is significantly higher than that of fertile men.